(untitled) (Global Journal of Management and Business Research, 2019)
The purpose of this paper is to investigate the effects of microcredit programs on women empowerment in Bangladesh, especially in rural areas, by making a comparative study of Grameen Bank and BRAC. In this study, both primary and secondary data were used. Primary data were collected by a household questionnaire survey in Tangail district. Percentage analysis, cross-tabulation, and paired ttest had been used to analyze and interpret the data. Secondary data were retrieved from different books and magazines, internet and related journals, and project papers. The results showed that microcredit programs of Grameen Bank and BRAC have a significant impact on women empowerment in Tangail district, Bangladesh. The research was limited to Tangail region, and only two NGOs were taken into consideration while collecting primary data. The policymakers can utilize these research findings while making policies on women empowerment. This study will also encourage different other NGOs to broaden their microcredit programs as well as the women to take microcredit and change their fortune.